Endothelial nitric oxide synthase is central to skeletal muscle metabolic regulation and enzymatic signaling during exercise in vivo - Lee-Young, Robert S. (American Physiological Society, 2010)
Endothelial nitric oxide synthase (eNOS) is associated with a number of physiological functions involved in the regulation of metabolism; however, the functional role of eNOS is poorly understood. We tested the hypothesis that eNOS is critical to muscle cell signaling and fuel usage during exercise in vivo, using 16-wk-old catheterized (carotid artery and jugular vein) C57BL/6J mice with wild-type (WT), partial (+/−), or no expression (−/−) of eNOS. Quantitative reductions in eNOS expression (∼40%) elicited many of the phenotypic effects observed in enos(−/−) mice under fasted, sedentary conditions, with expression of oxidative phosphorylation complexes I to V and ATP levels being decreased, and total NOS activity and Ca(2+)/CaM kinase II Thr(286) phosphorylation being increased in skeletal muscle. Despite these alterations, exercise tolerance was markedly impaired in enos(−/−) mice during an acute 30-min bout of exercise. An eNOS-dependent effect was observed with regard to AMP-activated protein kinase signaling and muscle perfusion. Muscle glucose and long-chain fatty acid uptake, and hepatic and skeletal muscle glycogenolysis during the exercise bout was markedly accelerated in enos(−/−) mice compared with enos(+/−) and WT mice. Correspondingly, enos(−/−) mice exhibited hypoglycemia during exercise. Thus, the ablation of eNOS alters a number of physiological processes that result in impaired exercise capacity in vivo. The finding that a partial reduction in eNOS expression is sufficient to induce many of the changes associated with ablation of eNOS has implications for chronic metabolic diseases, such as obesity and insulin resistance, which are associated with reduced eNOS expression.